A sensitive method for Sr-90 analysis by accelerator mass spectrometry. Issue 1 (2nd January 2021) - Sasa, Kimikazu; Honda, Maki; Hosoya, Seiji; Takahashi, Tsutomu; Takano, Kenta; Ochiai, Yuta; Sakaguchi, Aya; Kurita, Saori; Satou, Yukihiko; Sueki, Keisuke
ABSTRACT: Strontium-90 is one of the most important fission products due to the potential health risks of its uptake and retention in the human body. Conventional analysis techniques involve β counting, which requires ingrowth of 90 Y over a period of two weeks. Accelerator mass spectrometry (AMS) has the potential to shorten the analysis time while offering a lower limit of detection than β counting. Here, Sr in samples was recovered as SrF2 to provide sufficient negative ions in the caesium-sputtering ion source. In the sample preparation step, 95–98% of Sr was recovered and 99–100% of Zr removed by ion-exchange separation. Sr recovery was 30% in the precipitation process, and this can be improved. A maximum 500 nA beam current of SrF3 – ions was obtained from SrF2 samples mixed with PbF2 . A five-anode gas ionization detector was used to avoid isobaric interference from 90 Zr. The 90 Sr/Sr atomic ratio background of 6 × 10 –13 ( 3 mBq 90 Sr) was comparable with that achieved at other AMS facilities. Good linearity in 90 Sr/Sr atomic ratios was obtained from 1.75 × 10 –10 to 3.38 × 10 –9 . Suitable techniques for sample preparation and measurement were thus achieved for 90 Sr analysis by AMS.